The state of customer oriented-behavior in the health tourism hospitals in Malaysia - Ong, Choon Hee; Johari, Husna (Center for Enhancing Knowledge, UK, 2013)
The purpose of this paper is to examine the state of customer-oriented behavior in the health tourism hospitals in Malaysia.This study involved 343 nurses in the 13 health tourism hospitals in Malaysia.Administered on-site questionnaire survey was used as the main method of data collection.Descriptive analysis and test of significant differences were employed to investigate the state of customer-oriented behavior among nurses in the health tourism hospitals.The findings revealed that the level of customer-oriented behavior among the nurses was high and the re were significant group differences in the level of customer-oriented behavior among the nurses’ gender, age group and years of work experience. These findings may be of help to healthcare managers to train their nurses to become more customer-oriented.